"Achoramiento" and Corruption in Contemporary Peru - Medina, Oswaldo (2001)
This essay analyzes the corruption phenomenon occurred during the President Alberto Fujimori Regime. For this purpose, it uses the tentative hypothesis of "achoramiento", understood as a strategy to achieve social acceptation and upgrade that essentially violates ethnic and juridical norms. lt outlines the great bond and magnitude of these two phenomenons, both, products of the government's desire to monopolize control due to the corrupted political sphere, almost indeed a mafia, dominated an important part of Peruvian society.   lt specially focuses on the relationships of "achoramiento" that had the legal advisor of the Servicio de Inteligencia Nacional with a number of well-known businessmen who fell into the trap, to obtain economic and legal welfare. By using this, they lost their citizen condition and transformed in an added expression of social corruption in Peru. lt is well known and sustained that this portion of Peruvian entrepreneurs has historically considered the state as a mean to personal economic profit, leaving privacy and particularity as superior and universal values or aims.   Finally, this essay suggests that this behavior is not exclusively to Peruvian society but naturally adjustable to capitalist ideology, system that has deified money in the world, making this object at least in an absolute mean of power capable to corrupt conscience and social order.